No Independence without Sovereignty! The Resistance of Emperor Ḫaylä Śǝllase I to the British Occupation of Ethiopia (1941–1944) - Coleman, Jr., Sterling Joseph (Aethiopica, 2010)
This article examines how Emperor Ḫaylä Śǝllase I succeeded in removing the British military occupation of Ethiopia during World War II with only a minimum of bloodshed. It outlines the various strategies and tactics the Emperor of Ethiopia employed to regain control over his empire. The text also asserts that he engaged in a pre-Cold War variant of the policy of flexible response which permitted him to resist British military rule without provoking a violent response from his occupier. The text highlights a handful of the numerous tactics and strategies which were employed by indigenous leaders and their allies not only in Africa but also throughout the developing world to successfully resist European colonial rule during and after World War II.